CONCORDANCE OF SERUM ELECTROLYTES ON TWO DIFFERENT LAB EQUIPMENTS –DRY CHEMISTRY VS. ABG AND ITS IMPORTANCE IN PATIENT CARE - SANA PARVEEN,; PRISCILLA ABRAHAM CHANDRAN, (International Journal of Pharma and Bio Sciences, 2015)
Analyzing values of two different machines for the same parameter allocates clinician’s discretion for medical decisions and important tool for method validation. Electrolyte samples of 635 patients were measured using ABG and Dry chemistry analyzer. The Mean for Sodium by Dry chemistry analyzer was 134.6 (±7. 59) and by ABG analyzer 134.1 (±7. 57), that of Potassium 3.7 (±0. 7) and 3.5 (±0. 67) and for Chloride 100.4 (±8. 63) and 100 (±8. 79) respectively, showing no difference in Mean. The Bland Altman analysis with the 95 % limit of agreement between methods range from -3.4 to 4.2 (Sodium), -0.3 to 0.7 (Potassium) and -6.2 to 7 (Chloride), providing similar clinically relevant measures. The Deming regression curve showed intercept zero and slope one with (95%CI)3%, 0.5%and 4% CV for sodium, potassium and chloride respectively. Passing and Bablok regression with 95% CI has an intercept zero and slope one showing no systematic and proportional difference. The 95%of random differences are -3.6 to 3.6 (sodium), -0.4 to 0.4 (potassium) and -4.7 to 4.7 (chloride) are small, shows both methods are comparable. The values obtained by two different machines are in concordance and therefore interchangeable, hence can improve the turnaround time.